Spectral selectivity model for light transmission by the intermediate filaments in Muller cells - Khmelinskii, Igor (2019)
Presently we continue our studies of the quantum mechanism of light energy transmission in the form of excitons by axisymmetric nanostructures with electrically conductive walls. Using our theoretical model, we analyzed the light energy transmission by biopolymers forming optical channels within retinal Muller cells. There are specialized intermediate filaments (IF) 10-18 nm in diameter, built of electrically conductive polypeptides. Presently, we analyzed the spectral selectivity of these nanostructures. We found that their transmission spectrum depends on their diameter and wall thickness. We also considered the classical approach, comparing the results with those predicted by the quantum mechanism. We performed experimental measurements on model quantum waveguides, made of rectangular nanometer-thick chromium (Cr) tracks. The optical spectrum of such waveguides varied with their thickness. We compared the experimental absorption/transmission spectra with those predicted by our model, with good agreement between the two. We report that the observed spectra may be explained by the same mechanisms as operating in metal nanolayers. Both the models and the experiment show that Cr nanotracks have high light transmission efficiency in a narrow spectral range, with the spectral maximum dependent on the layer thickness. Therefore, a set of intermediate filaments with different geometries may provide light transmission over the entire visible spectrum with a very high (similar to 90%) efficiency. Thus, we believe that high contrast and visual resolution in daylight are provided by the quantum mechanism of energy transfer in the form of excitons, whereas the ultimate retinal sensitivity of the night vision is provided by the classical mechanism of photons transmitted by the Muller cell light-guides.